LITERATUR REVIEW : EFEKTIVITAS PIJAT AKUPRESUR TERHADAP KEJADIAN MUAL MUNTAH PADA IBU HAMIL TRIMESTER I - Amanda Risqiana; Rr. Catur Leny Wulandari; Muliatul Jannah (Dian Nuswantoro Semarang, 2022)
Introduction: Nausea and vomiting that occurs in pregnant women is a normal symptom and is often found in the first trimester of pregnancy. Nausea and vomiting in pregnancy are caused by changes in the endocrine system. The incidence of nausea and vomiting that occurs in Indonesia is much greater than the incidence in the world, namely 60-80% primigravida and 40-60% multigravida. How to cope with nausea and vomiting using non-pharmacological therapy, one of which is acupressure massage. Objective: To determine the effectiveness of acupressure massage on the incidence of nausea and vomiting in first trimester pregnant women. Methods: The method in writing this article is a review of the literature contained in the database of health journals, namely Google Scholar, pubmed, text books, profiles of the Ministry of Health, and the WHO website. The selected articles are based on free full text, open access, in English and Indonesian within the last 10 years. Results: The results of a literature study through databases in health journals found a total of 7 articles on pubmed, 7 articles on Google Scoolar. In the results of the study, there was a significant effectiveness of acupressure massage on the incidence of nausea and vomiting in pregnant women in the first trimester. Conclusion: Acupressure stimulates the regulatory system and activates endocrine and neurologic mechanisms, by stimulating the hypothalamus to secrete endorphins that provide a sense of relaxation. Keywords: Acupressure; Emesis gravidarum; First trimester pregnant women